Study on Off-design Condition Characteristics and Control Strategy of Fluegas Waste Heat and Water Recovery System of Coal-Fired Power Plants - Guozhu ZHANG; Juntai ZHANG; Yu WEN; Kaixuan YANG; Ming LIU; Jiping LIU (Zhongguo dianli)
A fluegas waste heat and water recovery system for the coal-fired power plant is studied in this paper. Based on the material, energy balance and equivalent heat drop method, the water-saving and coal-saving capacity of the system were calculated. Off-design models of the system were developed, influences of environmental temperature and control strategy on system performance and state parameters were evaluated. Results show that the water-saving potential of the system is 15.34 kg/s under the design condition, and the energy-saving potential is 2.75 g/(kW·h). When the ambient temperature changes, the temperature of some state points of the system will decrease with the ambient temperature. The coal saving of the low-temperature economizer will be reduced to 1.44 g/(kW·h) when the ambient temperature is –20°C. To prevent low-temperature corrosion of the system, the operation strategy was proposed, the fluegas temperature entering the electrostatic precipitator is increased to 90°C, which can ensure the safe operation of the system. However, the coal saving of the low-temperature economizer is lower than that of the unadjusted by 0.2 g/(kW·h).